Skrining Diabetes Melitus Sebagai Upaya Peningkatan Kesehatan Masyarakat Desa - Nursolihah, Iha; Sembiring, Dian Agnesa; Sabrina, Sabrina (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Sungaibuntu is a village in West Java. Health facilities in Sungaibuntu are not adequate, this village does not have clinic and a doctor's practice, this can be a gap in the community's lack of understanding of the importance of maintaining health, one of which is Diabetes Mellitus (DM). Therefore, providing education and screening for diabetes mellitus is important as an effort to detect these diseases. The aim of this activity is to increase public knowledge and understanding regarding risk factors, early detection and self-management so that DM can be prevented and treated well. The stages of activities that will be carried out include providing DM education, measuring BMI, measuring blood pressure, and measuring blood glucose levels. The results of the activity showed an increase in participants' knowledge before and after being given DM education, while the screening results showed that 47.9% of participants were obese, 60.6% of participants had high blood pressure, and 18.3% of participants had high blood glucose levels at the time of measurement. DM education and screening can increase public knowledge and understanding regarding prevention, management, complications and good self-management. In this case, the role of the patient, family and related parties is needed so that the impact of DM can be minimized.